A comparison of two approaches for modeling dementia progression in a changing patient context. (8th April 2022) - Wubben, Nina; Haaksma, Miriam; Ramakers, Inez H. G. B.; van der Flier, Wiesje M.; Verhey, Frans R. J.; Olde Rikkert, Marcel G. M.; Melis, René J. F.
Abstract: Objectives: To explain the heterogeneity in dementia disease trajectory, we studied the influence of changing patient characteristics on disease course by comparing the association of dementia progression with baseline comorbidity and frailty, and with time‐varying comorbidity and frailty. Methods: We used individual growth models to study baseline and time‐varying associations in newly diagnosed dementia patients ( n  = 331) followed for 3 years. We measured cognition using the Mini‐Mental State Examination (MMSE), daily functioning using the Disability Assessment for Dementia (DAD), frailty using the Fried criteria and comorbidity using the Cumulative Illness Rating Scale for Geriatrics (CIRS‐G). Results: Although baseline comorbidity and frailty were associated with decreased daily functioning at diagnosis, their effects clearly diminished over time. In contrast, when incorporating comorbidity and frailty as time‐varying covariates, comorbidity was associated with lower daily functioning, and frailty with both lower cognition and daily functioning. Being frail was associated with a 0.9‐point lower MMSE score ( p  = 0.03) and a 14.9‐point lower DAD score ( p  < 0.01). A 1‐point increase in CIRS‐G score was associated with a 1.1‐point lower DAD score ( p  < 0.01). Conclusions: Time‐varying comorbidity and frailty were more consistently associated with dementia disease course than baseline comorbidity and frailty. Therefore, modeling only baseline predictors is insufficient for understanding the course of dementia in a changing patient context. Key points: Changes in personal characteristics such as comorbidity and frailty during follow‐up explain, in part, the observed heterogeneity in trajectories of dementia progression. As comorbidity and frailty fluctuate over time and often increase with age, baseline measurements might not suffice when modelling their relationship with disease progression measurements. Our results show that unlike at‐diagnosis (i.e., baseline) levels of frailty and comorbidity, time‐varying levels are more consistently associated with changes in the course of dementia.